ANALISIS POTRET WATAK TOKOH DAN AMANAT DALAM FILM MIRACLE IN CELL NO. 7 KARYA HANUNG BRAMANTYO - Syahadah, Nilam Trika; Suhardi, Suhardi; Irawan, Dody (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
This research aims to identify the characters and messages in the film Miracle in Cell No. 7 by Hanung Bramantyo using an objective approach. The data collection technique used is documentation. The results of this research reveal various characters and messages in the film Miracle in Cell No. 7. The protagonist characters are as follows: Dodo has a humorous, kind, gentle, and loving nature. Young Kartika is intelligent and understanding. Adult Kartika is wise and firm. Hendro is firm and wise. Japra is caring. Zaki is humorous and loving. Bewok is irritable and humorous. Gepeng is humorous. Bule is intelligent. The antagonist characters are as follows: Willy is vengeful. Rusman is selfish. The tritagonist characters are as follows: Okto is caring and irritable. Amat is caring. Agus is firm. Several messages are conveyed, including: doing good deeds without expecting anything in return, not judging people solely by their appearances, not being afraid to uphold what is right, not giving up easily in achieving one's desires, and being fair without considering social status. Keyword: character, message, film